FILOSOFI CINA DALAM PERIBAHASA JEPANG - Eka Marthanty Indah Lestari (Universitas Andalas, 2016)
Brief, meaningful expression or sentence which includes comparison, parable, suggestion, principle of life, or rule of behaviour is called the proverb. Japan is a country that is highly influence by Chinese culture. One of these influences can be viewed from its proverbs that are widely spread and still known until now in the society. There are many Japanese proverbs which include teaching or philosophy from the Chinese folklores. The philosophy comes from the ethics of Confucius and Buddhism. This paper discusses ten proverbs with the philosophy from China. These ten proverbs are ishi ni tatsu ya, issui no yume, gashin shoutan, gyofu no ri, keikou to naru mo gyuugo to naru nakare, dasoku, chousan boshi, ten’i muhou, tougenkyou, and haisui no jin. The aspects related to these ten proverbs that will be discussed are their history, Chinese philosophy within the proverbs, the use of proverbs in the context of sentence, and the functions in which the proverbs have pragmatic and social functions.